Reflexives and intensifiers in word-formations with auto-: a historical perspective - Orqueda, Verónica; Squdrito, Karem (Boletín de Filología, 2018)
In this paper, we analyze reflexive and non-reflexive formations with the prefix auto- (the latter better known as “intensifiers" [König, 2011]) in the Diachronic Corpus of Spanish (referred to as CORDE). The aim is to determine whether the use of this prefix as an intensifier is diachronically secondary to its use as a reflexive.From a typological functional approach, in line with works such as Givón (2001), Haspelmath (2008) and König, Siemund and Töpper (2013), which support the semantic polyfunctionality of potential reflexive markers, we classified and characterized such formations according to their function and grammatical class, and distributed the sample into different time spans. As a result, we observed not only that nonreflexive cases with auto- are present already in the earliest texts (as reflexives are), but also that their use grows steadily through time. We conclude that, although the whole number of reflexives is larger than that of non-reflexives at all stages, formations with the intensifying auto- are not necessarily secondary from a diachronic perspective.